A Business Destiny Forecast Model - Sorooshian, Shahryar; Amira, Mohd Mustafa (Romanian Society for Quality Assurance - SRAC, 2017)
In every region, Small and Medium Enterprises (SME) make a huge contribution to the gross domestic-product (GDP) and employment. Basically Small Medium-sized Enterprises (SMEs) are non-subsidiary and also independent firm which employ fewer total of an employees. Usually this number are varies across countries. However not all of the involvement of SMEs are successful. So the purpose of this research is to identify the criteria of Performance Measurement System (PMS) that can predict the failure and success in small medium-sized enterprises (SMEs) in Malaysia and develop a model to predict success and failure of SMEs in Malaysia using theory of constraints approach. Basically theory of constraint is a method to identify, analyze and also eliminate the constraints that been identified stop the firm from getting any new additional values process. Therefore, using logit regression was used to analyze the data collection for this research. So that, it will help this research to develop new model in order to predict new SMEs destiny.